2016
DOI: 10.1021/acscatal.5b02058
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Study of Nickel N-Heterocyclic Carbene Catalyzed C–O Bond Hydrogenolysis of Methyl Phenyl Ether: The Concerted β-H Transfer Mechanism

Abstract: The catalytic C−O bond activation of aryl ethers attracts substantial interest as it is significant for the lignin degradation process. A nickel complex with N-heterocyclic carbene (Ni-SIPr) has been shown to selectively catalyze C−O bond hydrogenolysis of aryl methyl ether to obtain arene and alcohol as the only products. Here, the reaction mechanism of Ni-SIPr catalyzed C−O bond hydrogenolysis of methyl phenyl ether (PhOMe) was studied using density functional theory. In the presence of H 2 , the catalytic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…Further investigations of the reaction scope (e.g., organoboron, organozinc, and/or other C–O/C–N electrophiles) and synthetic applications of the present method to photoelectrical materials, are in progress. It should be noted that previous mechanistic studies on transition metal-catalyzed C–O/C–N bond cleavage reactions from our group 27 , 35 , 69 and others 35 , 43 , 46 , 47 , 49 have found that the oxidative addition of ethereal C–O bond to Ni generally suffers from high activation barriers. However, it can be greatly facilitated either by formation of the Ni(0)-ate complex with Grignard reagent or by NHC ligand.…”
Section: Discussionmentioning
confidence: 77%
“…Further investigations of the reaction scope (e.g., organoboron, organozinc, and/or other C–O/C–N electrophiles) and synthetic applications of the present method to photoelectrical materials, are in progress. It should be noted that previous mechanistic studies on transition metal-catalyzed C–O/C–N bond cleavage reactions from our group 27 , 35 , 69 and others 35 , 43 , 46 , 47 , 49 have found that the oxidative addition of ethereal C–O bond to Ni generally suffers from high activation barriers. However, it can be greatly facilitated either by formation of the Ni(0)-ate complex with Grignard reagent or by NHC ligand.…”
Section: Discussionmentioning
confidence: 77%
“…[24] In addition, concerted b-hydrogen elimination and reductive hydrogen-vinyl elimination/coupling pathways were found by an umber of computational studies on nickel-catalyzed reactions. [25] Rebound of the open phosphine arm in IM9 converts it into IM10,w hich extrudes CO via the dissociative transition state TS8 to form IM11.S ubstitution of COD by IM11 releases the borylation product PhBcat, regenerates the active species IM1,a nd closes the catalytic cycle.T hus, adetailed plausible mechanism for the title reaction has now been established computationally.I tr eveals ac omplex yet well-defined reaction system consisting of two portions:( a) the activation of aryl carboxylic acids by B 2 cat 2 (Figure 1) and (b) the catalytic cycle beginning with the active species IM1 (Figure 2, Figure 3, and Figure 4). Thebalanced equations for the two portions and the overall reaction are the following:…”
Section: Methodsmentioning
confidence: 99%
“…7), and C-O cleavage via oxidative addition would be most likely. Surawatanawong [118,119] as well as Chung [120] reported that the classical oxidative addition pathway is also viable for the Ni(0)/ NHC-catalyzed hydrogenolysis of aryl ethers (Fig. 14).…”
Section: Activation Of Aryl Ethersmentioning
confidence: 98%